On the Issue of the Substitution of Concepts in Determining the Subjects of the Political System of Society (Based on a Critical Analysis of Modern Legal Literature on the Theory of State and Law) - Vladimir Valentinovich Kozhevnikov (Budapest International Research and Critics University, 2020)
This scientific article is devoted to some theoretical problems of the theory of the political system of society. The purpose of the article is to show the true, objective position in relation to the subjects of the political system. To solve this goal, the following tasks were set: a critical analysis of the opinions of those authors who consider as such: 1) criminal communities; 2) public organizations with an insignificant political aspect. Moreover, both in the first and in the second case, it has been proven that scientists are engaged in the substitution of concepts, that is, they commit a logical error. Result: 1) criminal associations are not subjects of the political system of society; 2) according to the political criterion, it is necessary to distinguish only proper political and not proper political organizations; 3) general theoretical provisions, opposite to those stated, differing in illogicality, do not contribute to improving the quality of educational literature on the theory of state and law.